Neck management in metastatic cutaneous squamous cell carcinoma of the head and neck - Xu, Ning; Sun, Qiang (Frontiers in Oncology, 2024)
Objective Optimal neck management remains unclear in head and neck cutaneous squamous cell carcinoma (HNcSCC) with parotid metastasis. Our goal was to compare the impact of different cervical treatments on HNcSCC with parotid metastasis. Methods Patients were retrospectively included. The primary outcome variables were regional control (RC) and disease-specific survival (DSS). The impacts of observation, elective neck irradiation (ENI), and elective neck dissection (END) were analyzed using the Cox model and presented as hazard ratios (HRs) and 95% confidence intervals (CIs). Results In total, 268 patients were enrolled. In the Cox model for RC, compared with ENI, observation was associated with a significantly higher risk of regional recurrence (p = 0.001, HR = 2.50, 95%CI = 1.45–4.30). However, END showed a comparable influence on regional recurrence (p = 0.246, HR = 0.70, 95%CI = 0.38–1.28). In the Cox model for DSS, END demonstrated a similar HR of 0.62 (95%CI = 0.30–1.26) compared to ENI (p = 0.184). However, patients who underwent observation were associated with an additional nearly twofold risk of cancer-related mortality (HR = 2.85, 95%CI = 1.55–5.23). Subgroup analysis showed that ENI predicted comparable RC (p = 0.389) and DSS (p = 0.346) in patients with one or two metastatic parotid lymph nodes, but worse RC (p = 0.007) and DSS (p = 0.024) in patients with more than three positive lymph nodes. Conclusion In HNcSCC with parotid metastasis, elective treatment of neck lymph nodes with END or ENI should always be performed.